2016
DOI: 10.1063/1.4944929
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-monoenergetic proton beam from a proton-layer embedded metal foil irradiated by an intense laser pulse

Abstract: A target structure, ion-layer embedded foil (ILEF) is proposed for producing a quasi-monoenergetic proton beam by utilizing a bulk electrostatic field, which is generated by irradiating the target with an ultra-intense laser pulse, inside the plasma. Compared with the case of a single metal foil in which the proton layer is initially present on the surface, in the ILEF target, the proton layer is initially located inside a metal foil. A two-dimensional particle-in-cell (PIC) simulation shows that the target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Lee [L-I15] from Korea Atomic Energy Research Institute reported a new type of layered target for the generation of an energetic proton beam with narrow energy spread. In this target, the ion layer was embedded inside the foil target and ion acceleration if realized by utilizing a bulk electrostatic field in the plasma (Kim et al 2016). Under optimized target parameters, protons can be accelerated to around 300 MeV with quasi-monoenergetic spectrum under the peak laser intensity of 10 21 W/cm 2 based upon their numerical simulation.…”
Section: Laser-driven Ion Acceleration and Applicationsmentioning
confidence: 99%
“…Lee [L-I15] from Korea Atomic Energy Research Institute reported a new type of layered target for the generation of an energetic proton beam with narrow energy spread. In this target, the ion layer was embedded inside the foil target and ion acceleration if realized by utilizing a bulk electrostatic field in the plasma (Kim et al 2016). Under optimized target parameters, protons can be accelerated to around 300 MeV with quasi-monoenergetic spectrum under the peak laser intensity of 10 21 W/cm 2 based upon their numerical simulation.…”
Section: Laser-driven Ion Acceleration and Applicationsmentioning
confidence: 99%